2016
DOI: 10.4049/jimmunol.1600576
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer Subtypes Generate Unique Immune Responses

Abstract: Lung cancer – the leading cause of cancer-related deaths worldwide – is a heterogeneous disease comprised of multiple histologic subtypes that harbor disparate mutational profiles. Immune-based therapies have shown initial promise in the treatment of lung cancer patients but are currently limited by low overall response rates. We sought to determine whether the host immune response to lung cancer is predicated, at least in part, by histologic and genetic differences, as such correlations would have important c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
122
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(131 citation statements)
references
References 63 publications
9
122
0
Order By: Relevance
“…The present investigation highlights the notion that ADC and SCC have a different biologic and tissue background (28,50), including the immune context. In this regard, we documented that 36% of SCC samples displayed type III intrinsic induction, while in ADC the proportion of type IV and II was consistently higher (32% and 36%, respectively).…”
Section: Discussionsupporting
confidence: 51%
“…The present investigation highlights the notion that ADC and SCC have a different biologic and tissue background (28,50), including the immune context. In this regard, we documented that 36% of SCC samples displayed type III intrinsic induction, while in ADC the proportion of type IV and II was consistently higher (32% and 36%, respectively).…”
Section: Discussionsupporting
confidence: 51%
“…This would be in accordance with a higher number of immunogenic antigens in tumours with a high number of mutations. In addition, this is in accordance with the lack of CD8+ lymphocyte response in EGFR‐mutant mice models and human tumours …”
Section: Discussionsupporting
confidence: 84%
“…Database analysis showed that TMIT was significantly associated with somatic mutations, neoantigen, PD‐L1 amplification, and oncogenic viral infection, but it was a comprehensive analysis of all types of tumors. Different lung cancer subtypes have a different biologic background and tissue characteristics . Subsequent genomic analysis indicated that TMIT was associated with mutation and neoantigen numbers in LAC but not in SCC .…”
Section: Discussionmentioning
confidence: 99%